A three-pronged approach to waste composition determination. (1st February 2022) - Nell, Charlotte; Schenck, Catherina; Blaauw, Derick; Grobler, Lizette; Viljoen, Kotie
Abstract: Understanding solid waste composition has frequently been cited as one of the most valuable resources to those responsible for the proper management of solid waste. The unique contribution of this article lies in the fact that a waste characterisation study, conducted in a remote rural town in South Africa, was combined with an illegal dumping contents mapping and a household survey. This enabled researchers to gain a more thorough understanding of household waste management practices and challenges in this community, bridging the knowledge gap that is created when illegal dumping and household perceptions are omitted from waste characterisation studies in study areas where illegal dumping is an ongoing concern. The study therefore contributes to understanding the waste behaviour of households within the larger context of the town's waste management practices. Results indicate that, in order for municipalities to fully understand how to manage their waste, the contents of illegal dumping, where present, and household surveys should also be included in waste characterisation assessments. Highlights: Waste characterisation studies influence decisions which increase effectiveness in waste management. Combining waste characterisation, illegal content mapping and a household survey, guide improved waste management. Poor communities in South Africa struggle to manage several waste fractions. Managing illegal dumping needs to be done alongside the communities.